Maturation and spawning of Decapterus russelli(Ruppell, 1830) along the Malabar coast - Manojkumar, P P (Indian Journal of Fisheries, 2011)
Maturation and spawning of Decapterus russelli(Ruppell, 1830) along the Malabar coast